Adaptation of the exterior wall construction of the industrial building located in the city of Jizzah to the requirements of building codes 2.01.04 - 2018 “Thermal technique in construction” - Ziyaviddinov, Dilshod Orziqul o’g’li; Yunusov, Behruz Aziz o’g’li; Abdunabiyev, Akbarxon Qahramon o’g’li; Xudoyberdiyeva, Chinora Ahmadjon qizi (Science and Education, 2024)
This article shows the calculation work and its solution for increasing the overall heat transfer resistance of the external wall constructions of the industrial building designed for the production of natural materials, built of low-rise brick, located in the city of Jizzakh. This solution is aimed at increasing thermal protection for winter conditions in accordance with the requirements of BUILDING CODES 2.01.04-18 “Construction thermal engineering”.